The Struggle for Anti-racist Environmental and Housing Justice: A View from a Militant Research Project in Cluj-Napoca, Romania - Enikő Vincze; George Iulian Zamfir; Vasile Gâlbea (Critical Romani Studies)
This article presents the struggle for anti-racist environmental and housing justice in Cluj-Napoca, Romania, and argues for militant research that provides knowledge and arguments to transform political thinking and practices. In discussing their activist research, the authors offer a methodological toolkit for activist knowledge production that might serve actions for social justice beyond the Pata Rât case discussed – a place in the city of Cluj-Napoca, Romania, where Romani residents are forced to live in proximity to toxic landfills. The article presents how a local movement, of which the authors are part, conducted multidisciplinary militant research to support actions against racist environmental and housing injustice. The article discusses different understandings of these concepts and describes the formation of the residential area and Romani residents’ health conditions in the toxic environment of Pata Rât. The article also offers an interpretive synthesis of various types of empirical materials. In other words, militant research links environmental justice and housing justice via an anti-racist stance in the context of Romania. It stresses that without changing the structural  conditions created by capitalism that force racialised people to live in polluted environments, legal recognition of housing and environmental rights will not mitigate intersectional injustice.